2019
DOI: 10.1038/s41598-019-56465-0
|View full text |Cite
|
Sign up to set email alerts
|

Soybean yield, biological N2 fixation and seed composition responses to additional inoculation in the United States

Abstract: It is unclear if additional inoculation with Bradyrhizobia at varying soybean [Glycine max (L.) Merr.] growth stages can impact biological nitrogen fixation (BNF), increase yield and improve seed composition [protein, oil, and amino acid (AA) concentrations]. The objectives of this study were to evaluate the effect of different soybean inoculation strategies (seed coating and additional soil inoculation at V4 or R1) on: (i) seed yield, (ii) seed composition, and (iii) BNF traits [nodule number and relative abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…The results showed that there is no significant effect of the additional inoculant application at R3 on soybean yield and seed composition, except soybean in 2019 following a cover crop at Kentucky. These results are in agreement with previous studies that found no effect of inoculant applications at planting (Ham et al, 1971;De Bruin et al, 2010;Carciochi et al, 2019) or from additional inoculant applications at R1 (Carciochi et al, 2019) in fields with the previous history of soybean cultivation. The study of Moretti et al (2018) is one of the few studies evaluating supplemental inoculant spray applications after planting that found a significant effect on yield from this practice and in fields with previous soybean history.…”
Section: Effect Of Inoculant Applications At R3supporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that there is no significant effect of the additional inoculant application at R3 on soybean yield and seed composition, except soybean in 2019 following a cover crop at Kentucky. These results are in agreement with previous studies that found no effect of inoculant applications at planting (Ham et al, 1971;De Bruin et al, 2010;Carciochi et al, 2019) or from additional inoculant applications at R1 (Carciochi et al, 2019) in fields with the previous history of soybean cultivation. The study of Moretti et al (2018) is one of the few studies evaluating supplemental inoculant spray applications after planting that found a significant effect on yield from this practice and in fields with previous soybean history.…”
Section: Effect Of Inoculant Applications At R3supporting
confidence: 93%
“…The yield response to Bradyrhizobium japonicum bacteria inoculations applied to the seed or during early vegetative stages depends on the field history (Albareda et al, 2009;Hungria et al, 2013;Cordeiro and Echer, 2019). Studies with previous soybean history often find no yield advantage from seed or early season inoculations (Ham et al, 1971;De Bruin et al, 2010;Carciochi et al, 2019). Interestingly, the study of Moretti et al (2018) showed that additional spray inoculations of B. japonicum after planting increased nodule biomass and increased yield by 27% compared with a standard seed inoculation practice, even in a soil with a high Bradyrhizobia population.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between countries might explain the estimates that 80% of the Brazilian and Argentinian farmers adopt annual reinoculation, in contrast to 15% of the North American (Chang et al., 2015; Leggett et al., 2017). Another recent report from the USA indicated lack of response to reinoculation (Carciochi et al., 2019); however, in this study, a commercial inoculant was used and there was no check on the cell concentration before sowing, and one may be surprised by the low quality of some commercial inoculants. As high yields and seed protein in the USA seem limited by N that cannot be supplied by the naturalized bradyrhizobia population (La Menza et al., 2020; La Menza, Monzon, Specht, & Grassini, 2017), although edaphoclimatic conditions and soil fertility in the USA are usually very different from those of South America, it seems interesting to suggest the strategy of annual reinoculation to increase yields and protein content in grains.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, N-fixation and protein concentration are slightly correlated (Fabre and Planchon, 2000) and are prone to interactions with the environment (Assefa et al, 2019). It is worth noting that RAU had a narrow range of values concentrated near the upper boundary of previous reports (Carciochi et al, 2019;Moro Rosso et al, 2021). The fact that RAU was grouped with low importance for predicting yield (and protein) indicates that improvement in N-fixation in such environments would lead to a marginal increase to these traits.…”
Section: Discussionmentioning
confidence: 87%